ProGas v1.1: Program for the preprocessing and data analysis of in vitro gas production of ruminant foods. Technical note - García, Yaneilys; Torres, Mildrey; Rodríguez, R. (Cuban Journal of Agricultural Science, 2022)
ProGas v1.1 was developed to support researchers in the preprocessing and data analysis of in vitro gas production of ruminant foods. For the implementation of this program, Microsoft Office Excel 2007 was used. The conversion of data to volume (mL g-1 incOM) was carried out with an established equation. The duration of the gas production phases was estimated by means of the average variation rates and the critical points. A total of six sheets were designed in the program: general, enter pressures, accumulated volume, critical points, graphs and help. It is concluded that the proposed program allowed preparing the experimental data for its subsequent modeling. In addition, the methodology that was applied to estimate the critical points did not require a mathematical model to calculate the duration of the in vitro gas production phases, which facilitated the description of the degradation kinetics of the evaluated foods. Key words: processing, speed, critical points, phases, fermentation